2010
DOI: 10.1002/uog.7551
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional ultrasound in the diagnosis of Müllerian duct anomalies and concordance with magnetic resonance imaging

Abstract: Objectives To demonstrate the value of three-dimensional (3D) ultrasound in the diagnosis of uterine malformations and its concordance with magnetic resonance imaging (MRI). Methods (kappa index, 0.880 (95% CI, )). Discrepancies in diagnosis betweenthe two techniques occurred in four cases. There was very good concordance in the diagnosis of associated findings (kappa index, 0.878 (95% CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
125
2
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(143 citation statements)
references
References 34 publications
(44 reference statements)
7
125
2
7
Order By: Relevance
“…11,17 MRI offers a non-invasive approach of assessing the internal and the external contour of the uterus with a high degree of concordance between 3D ultrasonography and MRI in the diagnosis of uterine malformation. 18 In our study, only 74% accuracy in patients with infertility, while in those with RPL diagnoses were 76% correct and those complaining from abnormal uterine bleeding, the accuracy was 74% with MRI. The diagnosis of synaechae was the main factor in decreasing the accuracy values for 3D TVS and MRI exclusion of the synaechae the accuracy of the 3D TVS was 100% for all uterine anomalies with different complaint.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…11,17 MRI offers a non-invasive approach of assessing the internal and the external contour of the uterus with a high degree of concordance between 3D ultrasonography and MRI in the diagnosis of uterine malformation. 18 In our study, only 74% accuracy in patients with infertility, while in those with RPL diagnoses were 76% correct and those complaining from abnormal uterine bleeding, the accuracy was 74% with MRI. The diagnosis of synaechae was the main factor in decreasing the accuracy values for 3D TVS and MRI exclusion of the synaechae the accuracy of the 3D TVS was 100% for all uterine anomalies with different complaint.…”
Section: Discussioncontrasting
confidence: 46%
“…13,20 The efficacy of MRI for MDA evaluation with an overall accuracy of 100%, 3D ultrasound has the advantage over MRI as it is less expensive and better tolerated by patients. 18 3D ultrasound aided us to make measurements of the septum such as length and thickness. The volume of the cavity can be calculated as well as the study of septal vascularization, which can affect fertility prognosis, thus helping the choice of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Coronal T2W images of MRI are ideal for demonstrating the uterine septum dividing the endometrial cavity asymmetrically along with the blind ending cavity and haematometra. T1W images show the haematometra and haematosalpinx as bright fluid in the endometrial cavity and dilated fallopian tube.…”
Section: Discussionmentioning
confidence: 99%
“…The use of transvaginal 3DUS has proved to be extremely accurate in the detection and classification of uterine anomalies 26 and seems to have replaced endoscopy as the gold standard technique for diagnosis of septate uterus. 27 Septate uterus is sonographically diagnosed when a septum dividing the endometrial cavity is demonstrated on the coronal plane and the external uterine surface is normal or shows a sagittal notch of <1 cm. Septate uterus is further classified as complete or incomplete (subseptate uterus) depending on whether the septum bridged or did not bridge the fundus to the internal os of the uterine cervix.…”
Section: Discussionmentioning
confidence: 99%